Religious Socialisation of Children and Youth in Eastern Orthodox Christian Church as Educational and Pastoral Challenge of Sharing of Cultural Practices - Galabova, Liana (Central European Journal of Educational Research, 2020)
As a result of three decades of social-cultural transformation, Bulgarian literature and practice of religious education though still rare is increasing and improving. As the Church recovers, local parishes, monasteries, and convents become visibly re-socialised and motivated again to provide more adequate pastoral care for all ages. This study explores the importance of informal improvisation and innovation as an approach, in the best interest of children and youth, at a time when an effective, regulated mass public religious education system in Bulgaria is not likely to appear soon. At the same time, revitalised eparchial, parish, convent, and monastery centres start meeting actual needs of renewed church ethos, and begin to provide opportunities for religious socialisation of children and youth that is more functional. Based on direct and indirect experience, on observation, and on partial access to limited local empirical data (that is historically and/or anthropologically only partially explored and categorised), this paper contributes to the analysis of the following unresolved issue: how to direct research toward and keep account of well-known educational and pastoral practices, whether traditional or contemporary, that aid the effective and sustainable religious socialisation of children and youth.